Perbandingan Nilai Diskriminasi Modified NUTRIC Score dan Skor APACHE II Terhadap Mortalitas 28 Hari Pada Pasien Sepsis Yang Dirawat Di ICU - Mulyawan, Dadang; Pradian, Erwin; Zulfariansyah, Ardi (Faculty of Medicine, Universitas Padjadjaran, 2026)
Introduction: Sepsis with malnutrition increases complications and mortality in ICU patients. The modified Nutrition Risk in Critically Ill (mNUTRIC) score assesses nutritional risk and predicts mortality, whereas APACHE II does not account for nutritional status. This study compared mNUTRIC and APACHE II for predicting 28–day mortality in ICU patients with sepsis. Methods: This prospective observational study was conducted from February to April 2024. Sepsis patients admitted during the study period were included. Discriminatory performance for predicting 28–day mortality was evaluated using the area under the receiver operating characteristic curve (AUROC). Comparison between scoring systems was performed using DeLong’s non–parametric test.Results: A total of 39 ICU patients were included. The mean mNUTRIC score was 4.44±2.23, and the mean APACHE II score was 17.59±5.28. The AUROC value was 0.825 for the mNUTRIC score and 0.789 for the APACHE II score. DeLong’s test showed that the mNUTRIC score had significantly better discrimination for predicting 28–day mortality than the APACHE II score (p=0.011).Discussion: mNUTRIC integrates nutritional and chronic health factors, capturing patients’ physiological reserve more comprehensively than APACHE II. Early identification of high–risk patients may guide targeted interventions and ICU resource allocation.Conclusion: The mNUTRIC score demonstrated superior discriminatory ability compared to the APACHE II score in predicting mortality among sepsis patients in the ICU. Incorporating nutritional risk assessment may improve mortality prediction and clinical decision–making in critically ill sepsis patients.